Creating a "union in diversity": european identity in twentieth century narratives of travel - Collings, Rhian Sarah (2017)
In Europe: An Unfinished Adventure, Zygmunt Bauman demonstrates, through a series of examples from the Bible and Greek mythology, that “Europe is not something you discover; Europe is a mission – something to be made, created, built”.1 The Europe of today is undoubtedly built upon the policies, governments and leaders of its member states and upon the politics of the European Union’s governing body, but perhaps of the greatest importance in this construction of Europe is the often lesser-considered element of culture and cultural identity. A group of people with different nationalities and different mother tongues cannot experience a sense of togetherness, a sense of community, thanks to policymaking. A sense of cultural belonging is cultivated through more subtle means: through the accumulation over centuries of books, music, poetry and artwork that helps to create a common imagery and a landscape of the European mind. European thinkers, such as Zygmunt Bauman, Jürgen Habermas, Jacques Derrida, Roberto Dainotto and Amin Maalouf, have theorised the current status of Europe: but will their message regarding the importance of European belonging be heeded by the masses? Undeniably, sociology, philosophy, and literary theory do not speak to the public in the same way that literature can, since the latter is inevitably more engaging.